2012
DOI: 10.7314/apjcp.2012.13.8.3791
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of CD44v6/v7 in Acute Promyelocytic Leukemia

Abstract: CD44v, especially splice variants containing exon v6, has been shown to be related closely to development of different tumors. High levels of CD44v6/v7 have been reported to be associated with invasiveness and metastasis of many malignancies. The objective of this study was to detect expression of CD44v6-containing variants in patients with acute promyelocytic leukemia (APL) and evaluate the potential of CD44v6/v7 for risk stratification. Reverse transcription polymerase chain reaction (RT-PCR) followed by PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Fan et al performed a metaanalysis and demonstrated CD44v6 positive cells were significantly associated with poor overall survival in patients with colorectal cancer (OR=0.36, p=0.02) (Fan et al, 2012). Study by Chen suggested that CD44v6/v7 expression might be a prognostic indicator in patients with acute promyelocytic leukemia (Chen et al, 2012 consistent with longer survival in laryngeal squamous cell carcinoma patients. In lung cancer, the present studies showed CD44v6 may play an important role in lung carcinoma histogenesis and in determining the fate of neoplastic differentiation (Spaford et al, 1996).…”
Section: Discussionmentioning
confidence: 91%
“…Fan et al performed a metaanalysis and demonstrated CD44v6 positive cells were significantly associated with poor overall survival in patients with colorectal cancer (OR=0.36, p=0.02) (Fan et al, 2012). Study by Chen suggested that CD44v6/v7 expression might be a prognostic indicator in patients with acute promyelocytic leukemia (Chen et al, 2012 consistent with longer survival in laryngeal squamous cell carcinoma patients. In lung cancer, the present studies showed CD44v6 may play an important role in lung carcinoma histogenesis and in determining the fate of neoplastic differentiation (Spaford et al, 1996).…”
Section: Discussionmentioning
confidence: 91%
“…For instance, individuals carrying the rs13347 TT and CT genotypes demonstrate higher CD44v expression level compared to those with the rs13347 CC genotype (57). The presence of various complex patterns of CD44 variant exons, particularly exon v6, has been observed in the majority of leukemia samples (58). The combination of CD44v6 and HA enhances cell resistance to apoptosis and activates the PI3K/Akt signaling pathway (42).…”
Section: Expression Of Cd44 and Its Variants In Leukemia Cellsmentioning
confidence: 99%
“…There are a multiple unique features of this disease includes; potentially life-threatening coagulopathy, characteristic t(15;17) translocation, resulting in the PML-RARα΄ gene, unique sensitivity to all-trans-retinoic acid (ATRA), having potential for complete remission without chemotherapy and marrow aplasia and most curable (Bajpai et al, 2011;Chen et al, 2012;Imani-Saber and Ghafouri-Fard., 2014).…”
Section: Introductionmentioning
confidence: 99%